Spatio-temporal variability of natural radioactivity as tracer of beach sedimentary dynamics. (31st December 2019) - Arriola-Velásquez, A.; Tejera, A.; Guerra, J.G.; Alonso, I.; Alonso, H.; Arnedo, M.A.; Rubiano, J.G.; Martel, P.
Abstract: Knowledge of coastal sedimentary dynamics is an essential tool in the sustainable management of high-value natural places, such as beaches, which play an important role in human life. With this aim, spatio-temporal variations of activity concentrations of the main natural radionuclides in intertidal sand samples were measured in order to analyse their role as tracers of different sedimentary processes on a beach with wide and diversified sedimentary dynamics (Las Canteras beach at Gran Canaria Island). The radionuclides studied were 226 Ra, 232 Th, 40 K and 210 Pbex . A cluster analysis and a principal component analysis performed by using stationary averages of the studied radionuclides activity concentrations and other quantities, such as grain size and or bulk density, were developed. These analyses divided the beach into three zones of sediment distribution related to one of the main geomorphological characteristics of the beach. Finally, annual variations in 226 Ra/ 228 Ra ratios were used to study erosion and accretion periods on the beach. Graphical abstract: Image 1 Highlights: Natural radionuclides as tools for sustainable management of beaches. 226 Ra, 232 Th and 40 K trace different sedimentary zones depending on beach morphology. Temporal analysis of 228 Ra/ 226 Ra ratios traces beach accretion/erosion periods.